기혼 직장여성의 삶의 질 경로에 관한 연구 - 경북 경산시를 중심으로 - 허숙민; Heo Sook-min; 최원석; Choi Won-seok (여성학연구, 2014)
본 연구의 목적은 기혼 직장여성의 삶의 질에 관한 인과적 관계를 규명하기 위한 것이다. 이를 위해 조사대상은 경상북도 경산시에 거주하는 30세 이상 기혼 직장 여성을 임의표집 하였으며, 총 200부를 배포하여 회수된 설문지 중 유효 분석 자료 148부를 최종 분석 자료로 사용하였다. 분석방법으로는 측정변수를 검토하기 위한 평균 및 표준편차, t 및 F 검증, 상관관계 분석을 한 후 구조방정식 모형을 이용하였다. 분석결과, 기혼 직장여성의 성역할태도는 여성정책만족도를 거쳐서 삶의 질에 완전매개효과 경로가 형성되었으며, 지방정부 행정의 신뢰도가 여성정책만족도를 거쳐 삶의 질에도 완전매개효과가 있음을 알 수 있었다. 본 연구의 결과를 바탕으로 기혼 직장여성의 삶의 질 증진을 위한 방안을 제시해보면 우선, 기혼 직장여성의 삶의 질은 아직까지 우리 사회가 가사노동의 영역을 여성의 역할로 간주하는 데에서 기인하는 바가 크므로 여성발전기본법에 명시된 구체적인 정책들을 실행해 나가는 것이 필요하다. 둘째, 기혼 직장여성은 전통주의 성역할 태도를 견지할수록 여성정책만족도가 낮은 결과를 나타내고 있음을 고려해 볼 때 우리 사회는 잔존하고 있는 전통주의적 성역할 가치관을 변화시킬 수 있는 여성정책 방안이 요구된다. 셋째, 기혼 직장여성의 삶의 질은 지방정부 행정의 신뢰성이 여성정책만족도를 거치는 완전매개효과 경로를 감안할 때, 지방자치단체는 신뢰성 증진을 통하여 지역별 특성을 고려한 여성정책을 입안하는 것이 필요하다. 이를 위해 광역단체별 여성 가족정책연구기관의 연구가 활성화 되어야 할 것이다. The purpose of this study is to closely examine causality on quality of life in married working women. For this, the survey subjects were randomly sampled the married career women aged over 30 who dwell in Gyeongsan city of Gyeongsangbuk-do Province. It widely distributed totally 200 copies and then used 148 effective analytical materials as the final analytical data among the collected questionnaires. Structural Equation Model was used after analyzing the mean & standard deviation, t- and F-test, and correlation in order to examine the measurement variable as an analytical method. As a result of analysis, the married working women’s gender role attitude was formed the path of perfect mediating effect on quality of life after passing through the women policy satisfaction. The credibility of the administration in the local government could be known to have perfect mediating effect even on quality of life after passing through the women policy satisfaction. Suggesting a plan for promoting married working women’s quality of life based on the results of this study, first of all, the married career women’s quality of life originates greatly from which our society regards household labor as woman’s role yet. Thus, there is a need of supporting the working women so that work and family life can coexist. In such context, the policy-based measure is demanded that can lead to men’s participation in household chores and childrearing. Second, a women policy plan is demanded for vitalizing family-friendly system available for changing the traditional gender-role value that is left in our society, given considering that the more the married working women stick to the traditional gender-role value, the lower result the women policy satisfaction was shown. Third, the women policy of considering region-based characteristic needs to be mapped out, through promoting credibility in the local government, when considering the path of perfect mediating effect that the credibility in the local government passes through the women policy satisfaction on the married career women’s quality of life. For this, a study of research institution for women family policy by local government will need to be activated.